Prevalence of metabolic syndrome in pre- and postmenopausal women - Marchi,Ricardo de (2017)
ABSTRACT Objective The objective of this study was to determine the prevalence of metabolic syndrome (MS) and its components among pre- and postmenopausal women, as well as the association between menopausal status and MS. Materials and methods A retrospective study was conducted at a reference cardiology outpatient clinic in a city located in Northwestern Paraná State, Brazil. A total of 958 medical records of symptomatic climacteric women evaluated between 2010 and 2014 were analyzed. The study consisted of two groups: pre- and post-menopausal women. MS was characterized according to the criteria of the National Cholesterol Education Program’s Adult Treatment Panel III – NCEP-ATP III-2005. Results MS was observed in 18.5% of the total study population; 9.4% of the premenopausal women and 22.2% of the postmenopausal women displayed MS, corresponding to a relative risk of 2.75. In addition, the frequency of MS increased with age. Regarding the components of MS, postmenopausal women were more likely to have high density lipoprotein (HDL-C) levels < 50 mg/dL; systolic blood pressure (SBP) values ≥ 130 mmHg or diastolic blood pressure (DBP) values ≥ 85 mmHg; and fasting glucose levels ≥ 100 mg/dL. Conclusion MS was more prevalent among postmenopausal women than among premenopausal women.